Pengaruh Gaya Kepemimpinan Transformasional, Motivasi Dan Kompensasi TEerhadap Kinerja Karyawan - Catur Widayati; Thea H. Rahardjo; Melly Febriyanti (Jurnal Ekonomi, 2017)
This research aims to examine and analyze the influence of transformational leadership style, motivation and compensation on the performance of employees at PT.Hanken Indonesia Cibitung. The methods used in this research is the descriptive method. The object of this research is all staff office division who worked in PT. Hanken Indonesia Cibitung with a population of 125 people. Sampling technique using non-probability sampling with total samples is 95 people. The approach used in this research is a Structural Equation Models (SEM) with Smart analysis tools-PLS. The results showed transformational leadership style gives a positive and significant influence on employee performance. Work motivation has no significant on employee performance. Compensation provides a positive and significant effect on the performance of employees. This is evidenced from the results of hypothesis testing (t-test) which shows the significance value of the independent variables.